GRATITUDE: EMPIRICAL FINDINGS AND THEORETICAL PERSPECTIVES - Nikmah Rochmawati; Asmadi Alsa; Abd. Madjid (UIN Walisongo Semarang, 2018)
Expressing gratitude and responding it are rare things in Indonesia. It is interesting and surprising because in the Holy Quran there are so many verses about gratitude commands, moreover, God will give Muslim more if he is grateful. But we find most Muslims who are ungrateful. Based on this problem, this article aims to elaborate the significance of expressing gratitude and its correlation to the quality of faith to God, emotion, and happiness, and interpersonal relationship using the Quran and psychology as the conceptual framework and also based on empirical findings. The conclusion of this paper underlines that the Quran and psychology have common view on gratitude. The research results that grateful correlated with intrinsic religiousness positively and with extrinsic religiousness negatively and prayer increases gratitude, prayer plays a causal role in promoting gratitude as well. It is similar with the teaching of Surah An-Nisa’ (4): 147 and Surah Luqman (31): 12. People who often say thank you have strong relationship with the other as they do not only think of their relationship to God but also to other humans. All these findings are strongly in line with the research that gratitude is correlated to fewer depressive symptoms.AbstrakMengekspresikan rasa terima kasih dan menanggapinya adalah hal yang masih langka di Indonesia. Sangat menarik dan mengejutkan, karena da-lam Al-Quran ada begitu banyak ayat tentang perintah syukur, apalagi Tu-han akan memberi lebih banyak muslim jika dia bersyukur. Tapi kami menemukan sebagian besar muslim yang tidak tahu berterima kasih. Ber-dasarkan masalah ini, artikel ini bertujuan untuk menguraikan pentingnya mengekspresikan rasa terima kasih dan korelasinya dengan kualitas iman kepada Tuhan, emosi dan kebahagiaan, dan hubungan interpersonal menggunakan Al-Quran dan psikologi sebagai kerangka kerja konseptual dan juga berdasarkan temuan empiris. Kesimpulan dari artikel ini meng-garisbawahi bahwa Al-Quran dan psikologi memiliki pandangan yang sama tentang rasa terima kasih. Hasil penelitian yang bersyukur berko-relasi dengan religius intrinsik secara positif dan dengan religiusitas ekstrinsik negatif dan doa meningkatkan rasa syukur, doa memainkan peran kausal dalam mempromosikan rasa syukur juga. Ini mirip dengan ajaran Surah An-Nisa '(4): 147 dan Surah Luqman (31): 12. Orang yang sering mengucapkan terima kasih memiliki hubungan yang kuat dengan yang lain karena mereka tidak hanya memikirkan hubungan mereka dengan Tuhan tetapi juga untuk manusia lain. Semua temuan ini sangat sejalan dengan penelitian bahwa rasa terima kasih berkorelasi dengan gejala depresi yang lebih sedikit